Hexagonalization in AdS3×S3×T4: Mirror corrections - Fabri, Matheus [UNESP] (American Physical Society (APS), 2022)
A big open problem in AdS3×S3×T4 holographic duality is to compute the conformal field theory (CFT) data of the dual theory. In this direction in [B. Eden, D. l. Plat, and A. Sfondrini, J. High Energy Phys. 08 (2021) 049JHEPFG1029-847910.1007/JHEP08(2021)049] it was introduced the hexagonalization framework in the AdS3 context. It allows the computation of the structure constants of the CFT2 dual in the planar limit nonperturbatively, however in [B. Eden, D. l. Plat, and A. Sfondrini, J. High Energy Phys. 08 (2021) 049JHEPFG1029-847910.1007/JHEP08(2021)049] it was introduced only the asymptotic part of the hexagon valid for correlators with asymptotically large bridge lengths. In this work we complete this picture by computing the so called mirror corrections that allow to describe structure constants for finite bridge lengths and as a by-product we also prove that the half-BPS operators in the theory do not receive these corrections. We end up by giving the first steps on using hexagonalization to compute n-point functions in the AdS3×S3×T4 holographic duality.